Tuberculosis screening in a novel substance abuse treatment center in Malaysia: implications for a comprehensive approach for integrated care. - Al-Darraji, Haider Abdulrazzaq Abed; Wong, Kee Cheong; Yeow, David Gan Eng; Fu, Jeannia Jiani; Loeliger, Kelsey; Paiji, Christopher; Kamarulzaman, Adeeba; Altice, Frederick L (Journal of substance abuse treatment, 2014)
People who use drugs (PWUD) represent a key high risk group for tuberculosis (TB). The prevalence of both latent TB infection (LTBI) and active disease in drug treatment centers in Malaysia is unknown. A cross-sectional convenience survey was conducted to assess the prevalence and correlates of LTBI among attendees at a recently created voluntary drug treatment center using a standardized questionnaire and tuberculin skin testing (TST). Participants (N=196) were mostly men (95%), under 40 (median age=36 years) and reported heroin use immediately before treatment entry (75%). Positive TST prevalence was 86.7%. Nine (4.6%) participants were HIV-infected. Previous arrest/incarcerations (AOR=1.1 for every entry, p<0.05) and not being HIV-infected (AOR=6.04, p=0.03) were significantly associated with TST positivity. There is an urgent need to establish TB screening and treatment programs in substance abuse treatment centers and to tailor service delivery to the complex treatment needs of patients with multiple medical and psychiatric co-morbidities.
Keywords: Adult; Cross-Sectional Studies; Delivery of Health Care, Integrated; Female; HIV Infections; Humans; Latent Tuberculosis; Malaysia; Male; Mass Screening; Middle Aged; Prevalence; Questionnaires; Risk Factors; Substance Abuse Treatment Centers; Substance-Related Disorders; Tuberculin Test; Tuberculosis